Estudo das propriedades vibracionais do aminoácido DL-metionina por espectroscopia Raman - Gusmão, Gustavo Oliveira de Meira (2014)
In this work, DL-methionine crystals (C5H11NO2S) are investigated by Raman spectroscopy varying the thermodynamic parameters temperature and pressure. Raman scattering measurements were performed on DL-methionine amino acid (C5H11NO2S) in the form at room temperature in the spectral region between 40 and 3200 cm-1. Subsequently the vibrational modes and wave numbers of the isolated methionine molecule through density functional theory (DFT) calculations were computed by implementing the exchange-correlation functional B3LYP and the basis set of 6-31 G (d, p) with the aid the Gaussian 03. The computational calculations reproduced the characteristics of the material in good agreement with the experimental spectrum. Based on this agreement, it was possible to associate the observed wave numbers with atomic displacements in the molecules. Also for the molecule of DL-methionine calculations distribution of potential energy PED were performed, allowing classifying eigenmodes with greater precision and confront those that have been reported in the literature. Measurements of Raman scattering in the crystal of DL-methionine in the spectral region between 50 cm-1 and 3200 cm-1 were performed from room temperature to the temperature of 10 K. In the spectra, no significant changes were observed, only temperature effects associated with decreasing anharmonicity. In the Raman spectroscopy experiments varying the temperature between 298 K and 443 K, it was found that the crystal of DL-methionine has undergone a structural phase transition at around 338 K, which were detected in the Raman spectra through the changes exhibited by the peaks associated with vibrations mainly attributed to carboxyl (CO2-), NH3+ group, CS and CC bonds and CH2 and CH3 groups. The analysis of the Raman spectra obtained after returning to room temperature revealed the crystal DL-methionine retrieves the beta phase. The experiment of thermal analysis confirms the structural phase transition suggested by Raman spectroscopy experiments at high temperatures. Raman scattering as a function of hydrostatic pressure measurements were done in the DL-methionine crystal. The experiments were performed in the spectral range between 50 cm-1 and 1200 cm-1 compressing the sample from atmospheric pressure up to the pressure of 5.1 GPa and then decompressing it to atmospheric pressure. Changes related to the vibrations of the CO2- and NH3+ units and external modes changes show that the crystal undergoes a structural phase transition at 1.5 GPa involving some of the hydrogen bonds. The results of the decompression show that the phase transition is reversible.